1997
DOI: 10.2169/internalmedicine.36.179
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-13 but Not Interleukin-4 Prolongs Eosinophil Survival and Induces Eosinophil Chemotaxis.

Abstract: The effects of recombinant human (rh) interleukin (IL)-4 or rhIL-13 on survival, and chemotactic activity of human eosinophils were examined. Only rhIL-13 prolonged eosinophil survival in a dose-dependent manner above 3 ng/ml. Eosinophil survival induced by rhIL-13 was inhibited by monoclonal antibodies (mAbs) against IL-3 (p<0.0!) and granulocyte-macrophage colony-stimulating factor (GM-CSF) (p<0.05), suggesting that rhIL-13 induced IL-3 and GM-CSF production from eosinophils and an autocrine mechanism is res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 29 publications
4
75
1
Order By: Relevance
“…Changes in eosinophil trafficking, causing eosinophilia, involve three interacting components; upregulation of chemokine production by cytokines, eosinophil activation by chemokines and eosinophil adhesion (Blanchard & Rothenberg, 2009). Some of the cytokines involved in inflammatory mechanisms are IL4, IL5 and IL13, and these proteins are mainly synthesized by Th2 lymphocytes (Moser et al, 1992;Horie et al, 1997). Among the chemokines involved in eosinophil recruitment to inflammatory sites are the CXC-chemokines, RANTES, eotaxins and macrophage chemotactic proteins (MCPs; Rothenberg & Hogan, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Changes in eosinophil trafficking, causing eosinophilia, involve three interacting components; upregulation of chemokine production by cytokines, eosinophil activation by chemokines and eosinophil adhesion (Blanchard & Rothenberg, 2009). Some of the cytokines involved in inflammatory mechanisms are IL4, IL5 and IL13, and these proteins are mainly synthesized by Th2 lymphocytes (Moser et al, 1992;Horie et al, 1997). Among the chemokines involved in eosinophil recruitment to inflammatory sites are the CXC-chemokines, RANTES, eotaxins and macrophage chemotactic proteins (MCPs; Rothenberg & Hogan, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Murine studies have revealed that IL-5 promotes the maturation of eosinophils from bone marrow precursors (21), induces the recruitment of eosinophils (22), and promotes the survival of eosinophils (21,22). In addition to the known roles for IL-5, studies have demonstrated that IL-13 is a chemoattractant for and prolongs the survival of human eosinophils (23). Recent murine studies have suggested that IL-13 may also play an important role in RSV-induced pulmonary injury (24 -28).…”
Section: R Espiratory Syncytial Virus (Rsv)mentioning
confidence: 99%
“…RSV G 183-195 -specific memory Th2 cells are recruited to the lung by the production of CCL11, CCL17, and/or CCL22 and produce IL-4, IL-5, and/or IL-13. IL-5 induces the production of eosinophils from precursors in the bone marrow [62] and is necessary for the recruitment of eosinophils into the lung [63,64]. The production of IL-13 by G 183-195 -specific memory Th2 cells and other inflammatory cells is required for the development of pulmonary eosinophilia.…”
Section: Mechanisms Of Rsv Vaccine-enhanced Diseasementioning
confidence: 99%